Regorafenib in Chinese patients with metastatic colorectal cancer: Subgroup analysis of the phase 3 CONCUR trial. Issue 8 (28th January 2020) - Xu, Jianming; Xu, Rui‐Hua; Qin, Shukui; Pan, Hongming; Bai, Yuxian; Chi, Yihebali; Wang, Liwei; Bi, Feng; Cheng, Ying; Liu, Tianshu; Ma, Dong; Shen, Lin; et al.
Abstract: Background and Aim: In the phase 3 CONCUR trial (NCT01584830), regorafenib improved overall survival (OS) versus placebo in Asian patients with treatment‐refractory metastatic colorectal cancer (mCRC). We conducted a post hoc subgroup analysis of Chinese patients in CONCUR. Methods: Adults with mCRC progressing despite at least two prior treatment regimens and Eastern Cooperative Oncology Group performance status 0–1 were randomized 2:1 to regorafenib 160 mg once daily or placebo for the first 3 weeks of each 4‐week cycle. Dose modifications were permitted. The primary endpoint was OS. Secondary endpoints included progression‐free survival, objective overall response, disease control rate, and safety. Results: A total of 172 Chinese patients were randomized and treated (regorafenib n  = 112, placebo n  = 60). OS was significantly improved with regorafenib versus placebo (8.4 vs 6.2 months, respectively; hazard ratio [HR] 0.56, 95% CI 0.39–0.80; one‐sided P  = 0.000632), as was progression‐free survival (HR 0.32, 95% CI 0.22–0.47; one‐sided P  < 0.000001). The most common drug‐related grade ≥ 3 treatment‐emergent adverse events (TEAEs; regorafenib, placebo) were hand–foot skin reaction (19%, 0%), hypertension (13%, 3%), hypophosphatemia (7%, 0%), increased alanine aminotransferase (6%, 0%), and increased aspartate aminotransferase (5%, 0%). In patients receiving regorafenib and placebo, respectively, TEAEs led to treatment discontinuation in 14% and 7%, dose reduction in 39% and 0%, and dose interruption in 64% and 20%. Conclusions: This retrospective analysis showed that regorafenib provided an OS benefit over placebo for Chinese patients with previously treated mCRC. TEAEs were consistent with the regorafenib safety profile and manageable with treatment modifications.